Latent Growth Curve Analyses of Emotional Support for Informal Caregivers of Vulnerable Persons with HIV/AIDS - Mitchell, Mary M. (AIDS Care, 2015)
Persons living with HIV/AIDS (PLHIV) have growing rates of morbidity and need for informal care, especially among drug using PLHIV. Informal caregivers, or persons providing unpaid emotional or instrumental support, have protective effects on the health and well-being of PLHIV or other serious chronic conditions. Research suggests that social support, including care recipients' reciprocity of emotional support, is important to sustained caregiving. This study examined HIV caregivers' perceived emotional support over time from their current or former injection drug using care recipients. Methods: Data were from baseline, six-, and 12-months follow-up of the BEACON study. Results: Latent growth curve analysis showed a decline in reciprocated emotional support reports over time, particularly among caregivers themselves HIV seropositive or currently substance using. Researchers should develop interventions to strengthen the caregiving relationship by promoting reciprocity of emotional support, with implications for sustaining caregiving to vulnerable PLHIV and improving their health outcomes. Interventions should especially target dyads in which caregivers are also HIV positive and using substances.